The Meanings and Structural Forms of the Measure Word for Nouns in Chinese and Vietnamese - Le Pham, Quoc Hung (International Journal of Linguistics, 2021)
In the field of language research, the measure word is an interesting research topic. In the world language, some languages have measure words, some languages have not. Both Chinese and Vietnamese belong to the language rich in measure words, but due to the differences in language system, cognition and cultural color, there are some differences in the expression of their syntactic structure of the measure word for noun. This study starts from the comparison of Chinese and Vietnamese languages, focusing on the meaning and structure of the measure word for noun commonly used in Chinese and Vietnamese, in order to find the similarities and differences between them.